Amazing MSC – phenomenology, problems, solutions and opportunities - Kordium, V.A.; Irodov, D.M. (Вiopolymers and Cell, 2017)
The review briefly describes the history of prediction and discovery of mesenchymal stem cells (MSCs). The evolution of our views on the nature, functions, and status of MSCs in the organism is presented. We propose that MSCs represent transient states of different cells. The MSCs are involved in tissue repair by programmed replacement of the dying or dead cells). They also induce o renewal of specialized differentiated cells by action of specific signal molecules). MSCs might also participate in the continuous renewal of an organism during its lifetime.